Fluorosilicone acrylate polymer emulsion as well as coating and preparation method thereof
By copolymerizing short fluorocarbon chains and silicon-containing acrylate monomers in fluorosilicone acrylate polymer emulsion and surface modification, the problems of insufficient hydrophobic properties and environmental hazards of the existing fluorosilicone polymer emulsion are solved, and an efficient and environmentally friendly superhydrophobic coating is achieved.
Patent Information
- Application Number
- CN202411849530.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-28
AI Technical Summary
It is difficult for the existing fluorosilic polymer emulsion to effectively reduce the surface energy of the coating surface during the film formation process, resulting in insufficient hydrophobic performance and environmental hazards of long fluorocarbon chain polymers.
The fluorosilic acrylate monomer containing short fluorocarbon chains is used to copolymerize with the silicon-containing acrylate monomer, and a fluorosilic acrylate polymer emulsion with a core-shell structure is generated through polymerization, and modified on the surface to improve hydrophobic properties.
It achieves excellent hydrophobic properties while maintaining environmental protection performance. The water contact angle of the coating can exceed 150°, meeting the requirements of superhydrophobic surfaces, while reducing the cost of the polymer system.
Smart Images

Figure CN119529620A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a fluorosilicone acrylate polymer emulsion and a coating thereof, and specifically to an emulsion polymerization of a fluorine-containing acrylate monomer, a silicon-containing acrylate monomer and a non-fluorine-containing silicon acrylate monomer and the application of the modified product in a super-hydrophobic coating. Background Art
[0002] Functional surfaces with ideal wetting properties have received extensive attention in both basic research and practical applications. The two major factors that affect surface wettability are surface microscopic roughness and surface chemistry. By intervening in these two aspects, surfaces with special wettability can be prepared. Inspired by the super-hydrophobic plant surfaces in nature, such as the lotus leaf surface, researchers have found that super-hydrophobic surfaces can be achieved by reducing the surface free energy to provide hydrophobicity or constructing micro-nano roughness.
[0003] In the molecules of organic fluorine compounds, F atoms are closely arranged around the carbon chain to form a helical fluorocarbon chain structure, which shields the carbon chain, thus giving the organic fluorine compounds a lower surface energy. In addition, they have liquid corrosion resistance, stable weather resistance and excellent mechanical properties, making them candidate materials for constructing super-hydrophobic surfaces. Among the many fluorinated polymers, fluorinated acrylate (FA) polymers have received widespread attention due to their high hydrophobicity, good film-forming properties and strong adhesion on various substrates.
[0004] Although fluorinated acrylate polymers have excellent hydrophobic and oleophobic properties, the fluorinated acrylate polymers widely used at present are mainly fluorinated (meth) acrylate polymers with long fluorocarbon chains (number of carbon atoms ≥ 8), which will generate compounds containing long fluorocarbon chains during the degradation process. Studies have shown that perfluorooctanoate (PFOA), perfluorooctane sulfonate (PFOS) and other molecules containing long perfluoroalkyl chains can accumulate in wild animals, plants and humans, and have the potential risk of endangering human health and polluting the environment. Compared with compounds with long fluorocarbon chains, compounds containing short fluorocarbon chains (number of carbon atoms ≤ 6) have good degradability, and the corresponding short fluorocarbon chain polymers have less environmental hazards, but the problem is that the migration ability of short fluorocarbon chains is weak, and it is difficult to migrate to the surface during the film formation process, so it is impossible to effectively reduce the surface energy of the coating surface, so its hydrophobic ability is insufficient. Therefore, the preparation of fluorinated polymers with short fluorocarbon chains and excellent hydrophobic properties has become a major research hotspot.
[0005] However, the contact angle of acrylate polymers on substrates is limited to a maximum of 120°. Therefore, it is also necessary to construct micro-nanoscale roughness on the polymer surface to increase its contact angle. Organic / inorganic nanoparticles are increasingly attracting the attention of researchers as a simple method to increase roughness. Among inorganic nanoparticles, silica is the most widely used in research and industry. There are two main methods for preparing polymer / silica composite particles. One is to simply mix nanosilica and polymers, and the other is to introduce vinyl-containing monomers for copolymerization. Among these monomers, methacryloxy-functional silanes have received widespread attention because their vinyl groups can participate in polymerization, and the silane groups can also react with inorganic silicon compounds to form a structure similar to silica, improve surface roughness, and thus construct nanoscale roughness to improve surface hydrophobicity. Therefore, fluorosilicone polymers can appropriately improve surface roughness while reducing surface free energy, thereby obtaining more ideal hydrophobic properties. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a fluorosilicone acrylate polymer emulsion containing a short fluorocarbon chain, excellent hydrophobicity and a simple preparation method and a preparation method thereof, so as to overcome the defects of the existing fluorosilicone polymer emulsion.
[0007] In order to solve the above technical problems,
[0008] In a first aspect, the present invention provides a fluorosilicone acrylate polymer emulsion having a core-shell structure, wherein the core phase is a polymer having the following general chemical structure formula:
[0009]
[0010] Wherein, R is hydrogen or methyl, R1 and R2 are each selected from any group of C1 to C18 alkyl, m = any integer in the range of 30 to 50, and n = any integer in the range of 80 to 100;
[0011] The shell phase is a polymer having the following general chemical structure:
[0012]
[0013] Wherein, R is hydrogen or methyl, R3 and R4 are selected from any group of C1~C18 alkyl, R5 is selected from any group of C12~C18 alkyl, Rf is a group having a C(CF3)2CF2CF2CF3 structure, m=any integer in the range of 40~50, n=any integer in the range of 40~50, a=any integer in the range of 30~40, b=any integer in the range of 4~20, and c=any integer in the range of 10~20.
[0014] In a second aspect, the present invention further provides a method for preparing the fluorosilicone acrylate polymer emulsion described in the first aspect, which specifically comprises the following steps:
[0015] (4) Add acrylic acid ester monomer The reaction is heated in a solvent to produce product Ⅰ;
[0016] (5) Add acrylic acid ester monomer and fluorinated acrylate monomers And silicon-containing acrylate monomers The product II is generated by heating the reaction in a solvent;
[0017] (6) In a reactor, product I is mixed with an emulsifier and an initiator, and after initiation, product II is added to continue the polymerization reaction, and finally tetraethyl silicate is added to modify the surface layer to obtain the fluorosilicone acrylate polymer emulsion.
[0018] Furthermore, in step (1) and step (2), the acrylic acid ester monomer Any one selected from methyl methacrylate, ethyl methacrylate, butyl methacrylate, hexyl methacrylate, isooctyl methacrylate, lauryl methacrylate, octadecyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, hexyl acrylate, isooctyl acrylate, lauryl acrylate, and octadecyl acrylate.
[0019] Furthermore, in step (2), the acrylic acid ester monomer The silicon-containing acrylic ester monomer is selected from any one of lauryl methacrylate, octadecyl methacrylate, lauryl acrylate and octadecyl acrylate; and the silicon-containing acrylic ester monomer is selected from any one of 3-(trimethoxysilyl)propyl methacrylate and 3-(triethoxysilyl)propyl methacrylate.
[0020] Furthermore, in step (2), the acrylic acid ester monomer The weight ratio of the fluorine-containing acrylate monomer to the silicon-containing acrylate monomer is 1:2 to 1:10; the weight ratio of the fluorine-containing acrylate monomer to the silicon-containing acrylate monomer is 1:1.4 to 5:1.4.
[0021] Furthermore, the weight ratio of tetraethyl silicate to the silicon-containing acrylic ester monomer is 0.8:1.4 to 1.6:1.4.
[0022] Furthermore, in step (1) and step (2), the reaction temperature is 40-60° C. and the reaction time is 30-60 min.
[0023] Furthermore, in step (3), the usage ratio of product I and product II is calculated based on the usage ratio of the acrylic acid ester monomers used, that is, the usage ratio of the acrylic acid ester monomers used to prepare product I is and the acrylic acid ester monomer used in preparing product II The molar ratio is 2:1.
[0024] Furthermore, in step (3), the polymerization reaction temperature is 70 to 100° C. and the time is 10 to 30 hours.
[0025] Furthermore, in step (3), the amount of the initiator added is 0.1% to 3% of the total mass of all monomers; the amount of the emulsifier added is 3% to 4% of the total mass of all monomers; the initiator is selected from one or more of organic peroxides, inorganic peroxides and azo compounds; the emulsifier is selected from one or more of anionic emulsifiers, cationic emulsifiers and non-ionic emulsifiers.
[0026] In a third aspect, the present invention provides a coating, which is made by coating and then drying the fluorosilicone acrylate polymer emulsion described in the first aspect.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) In the fluorosilicone acrylate emulsion, the fluorine-containing group has a branched short-chain structure. Studies have shown that the longer the fluorine-containing chain segment, the more difficult it is to degrade and bioaccumulate, and therefore the more harmful it is. The fluorine-containing groups in the currently common fluorosilicone emulsions are long straight-chain fluorine-containing groups. In comparison, the fluorine-containing groups in the present invention have shorter fluorine-containing chain segments and excellent environmental performance. In addition, the present invention uses a polymerization method to introduce an inorganic silicon structure into the polymer emulsion, which works together with the function of reducing the surface energy of the fluorine-containing group, so that the coating prepared by the emulsion has excellent hydrophobic properties.
[0029] (2) The fluorosilicone polymer emulsion provided by the present invention is copolymerized by an acrylate monomer containing inorganic silicon and an acrylate monomer containing organic fluorine. While providing low surface energy, it has a certain degree of roughness, thereby obtaining excellent hydrophobic properties. In addition, the polymer itself can meet the requirements of hydrophobic properties, the preparation method is simple and the cost is further reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the infrared spectrum of the polymer PA prepared in Comparative Example 1 of the present invention;
[0031] Figure 2 is the infrared spectrum of the fluorosilicone polymer PFSA1 in Example 1 of the present invention;
[0032] Figure 3The water contact angles of the coatings prepared from the emulsions of the comparative example and Examples 1-9 of the present invention were tested. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] If the specific conditions are not specified in the examples, the conventional conditions or the conditions recommended by the manufacturer shall be followed. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased from the market. The fluorinated alcohol synthesized in the laboratory according to the patent (publication number CN110540614A) was used as the The product is prepared by reacting methacryloyl chloride with dichloromethane as solvent in the presence of a base.
[0035] Comparative Example 1
[0036] The synthesis of polymer PA, its core structure is as follows:
[0037]
[0038] Its shell structure is as follows:
[0039]
[0040] The synthesis process comprises the following steps: (1) placing 1.232 g of butyl methacrylate (BMA), 0.328 g of MMA methyl methacrylate, 0.038 g of DNS-86, and 1.5 g of deionized water in a beaker and heating at 40°C for 1 h to form product I; (2) adding 0.528 g of BMA butyl methacrylate, 0.396 g of MMA methyl methacrylate, 0.1 g of SMA octadecyl methacrylate, 0.28 g of KH-570 3-(trimethoxymethylsilyl) propyl methacrylate, 0.038 g of Add DNS-86 and 1.5g deionized water to a beaker and react at 40℃ for 1h to form product II; (3) Add 0.038g DNS-86, 1 / 2 initiator APS ammonium persulfate aqueous solution (0.044g APS dissolved in 3g water) and product I to a 50ml three-necked flask equipped with a reflux condenser, and heat to 70℃ in the reactor for 2h; add the remaining APS aqueous solution and product II to the system, heat to 80℃ and react for 2h; cool to 50℃, add 0.16g TEOS to the reaction system, and continue to react for 12h. A milky white liquid PA is obtained, and its infrared spectrum is as follows Figure 1 shown.
[0041] Example 1
[0042] Preparation of fluorosilicone emulsion PFSA1, its core structure is consistent with PA, and its shell structure is as follows:
[0043]
[0044] The synthesis process comprises the following steps: (1) placing 1.232 g of BMA butyl methacrylate, 0.328 g of MMA methyl methacrylate, 0.038 g of DNS-86 and 1.5 g of deionized water in a beaker and heating at 40° C. for reaction for 1 hour to form product I; (2) adding 0.528 g of BMA butyl methacrylate, 0.396 g of MMA methyl methacrylate, 0.1 g of SMA octadecyl methacrylate, 0.1 g of FMA fluorinated methacrylate, 0.28 g of KH-570 3-(trimethoxysilyl)propyl methacrylate, 0.038 g of DNS-86 and 1.5 g of deionized water in a beaker and reacting at 40° C. for 1 hour to form product II; (3) adding 0.038 g of DNS-86, 1 / 2 initiator APS ammonium persulfate aqueous solution (0.044g APS dissolved in 3g water) and all product I were heated in a reactor at 70℃ for 2h; the remaining APS aqueous solution and all product II were added to the system, heated to 80℃ for 2h; cooled to 50℃, 0.16g TEOS was added to the reaction system, and the reaction continued for 12h. A milky white liquid PFSA1 was obtained, and its infrared spectrum is shown as follows: Figure 2 shown.
[0045] Example 2
[0046] Preparation of fluorosilicone emulsion PFSA2, its core structure is consistent with PA, and its shell structure is as follows:
[0047]
[0048] The synthesis process is similar to that of Example 1, except that in step (2), the amount of fluorinated methyl acrylate added is 0.2 g, and finally a milky white liquid PFSA2 is obtained.
[0049] Example 3
[0050] Preparation of fluorosilicone emulsion PFSA3, its core structure is consistent with PA, and its shell structure is as follows:
[0051]
[0052] The synthesis process is similar to that of Example 1, except that in step (2), the amount of fluorinated methyl acrylate added is 0.3 g, and finally a milky white liquid PFSA3 is obtained.
[0053] Example 4
[0054] Preparation of fluorosilicone emulsion PFSA4, its core structure is consistent with PA, and its shell structure is as follows:
[0055]
[0056] The synthesis process is similar to that of Example 1, except that in step (2), the amount of fluorinated methyl acrylate added is 0.4 g, and finally a milky white liquid PFSA4 is obtained.
[0057] Example 5
[0058] Preparation of fluorosilicone emulsion PFSA5, its core structure is consistent with PA, and its shell structure is as follows:
[0059]
[0060] The synthesis process is similar to that of Example 1, except that in step (2), the amount of fluorinated methyl acrylate added is 0.5 g, and finally a milky white liquid PFSA5 is obtained.
[0061] Example 6
[0062] Preparation of fluorosilicone emulsion PFSA6, its core structure is consistent with PA, and its shell structure is as follows:
[0063]
[0064] The synthesis process is similar to that of Example 4, except that in step (3), the amount of tetraethyl silicate added is 0.2 g, and finally a milky white liquid PFSA6 is obtained.
[0065] Example 7
[0066] Preparation of fluorosilicone emulsion PFSA7, its core structure is consistent with PA, and its shell structure is as follows:
[0067]
[0068] The synthesis process is similar to that of Example 4, except that in step (3), the amount of tetraethyl silicate added is 0.24 g, and finally a milky white liquid PFSA7 is obtained.
[0069] Example 8
[0070] Preparation of fluorosilicone emulsion PFSA8, its core structure is consistent with PA, and its shell structure is as follows:
[0071]
[0072] The synthesis process is similar to that of Example 4, except that in step (3), the amount of tetraethyl silicate added is 0.28 g, and finally a milky white liquid PFSA8 is obtained.
[0073] Example 9
[0074] Preparation of fluorosilicone emulsion PFSA9, its core structure is consistent with PA, and its shell structure is as follows:
[0075]
[0076] The synthesis process is similar to that of Example 4, except that in step (3), the amount of tetraethyl silicate added is 0.32 g, and finally a milky white liquid PFSA9 is obtained.
[0077] The polymer emulsions prepared in the above embodiments and comparative examples were subjected to hydrophobic tests, as follows:
[0078] The polymer emulsions prepared in Examples 1 to 9 and Comparative Example 1 were respectively mixed with ethyl acetate to form a solution with a mass concentration of 5% to obtain a coating solution. The preparation method of the glass slide is as follows: the glass slide is immersed in ethanol for cleaning and then taken out with clean tweezers, oven dried, and aired to room temperature. The coating method is as follows: the coating solution is loaded into a spray can, and sprayed evenly at a distance of 20 cm from the glass slide at a pressure of 200 kPa, and the sprayed glass slide is baked in an oven at 80°C for 3 hours, and then annealed at 120°C for 30 minutes. According to the above preparation method, 3 coated glass slides are prepared for each solution.
[0079] The contact angle between the membrane and water was tested separately. Each solution was measured three times and the average value was taken. The test conditions were: liquid volume 3 μl, height 0.5 cm, magnification 7 times, and the results were as follows: Figure 3 As shown in Table 1 below;
[0080] Table 1
[0081]
[0082]
[0083] When the contact angle is used as an index for evaluating hydrophobicity, it can be seen from the sample test results of Comparative Example 1 and Examples 1-5 that when the fluorinated monomer FMA is not added, the water contact angle of the coating is 97.4°, and the coating has certain hydrophobic properties, but the hydrophobic properties are not particularly ideal. After adding the fluorinated monomer FMA, the contact angle is increased to 112.9°, and it is continuously increased to 117.6° with the increase of the content of the fluorinated monomer FMA. This is because the fluorinated polymer has a lower surface energy, and its hydrophobic properties are more excellent than those of fluorine-free polymers, and the macroscopic performance is that the water contact angle is larger. In addition, there are short fluorine chains in the polymer structure of the present invention, and the number of carbon fluorine atoms in the fluorinated acrylate monomer is 6, but the number of straight-chain carbon atoms in the fluorocarbon chain is only 3. Compared with the reference (CN110540614A), the straight chain in the fluorocarbon chain of the present invention is shorter, which can greatly improve the environmental safety characteristics. According to the sample test results of embodiment 4 and embodiment 6-9, it can be seen that the water contact angle of the polymer emulsion coating is 116.7 ° when the TEOS amount is 0.16g, and along with the increase of the TEOS amount, the water contact angle rises suddenly, all greater than 140 °. This is because the silicon-containing acrylate monomer in TEOS and the polymer can react, forming a structure similar to silicon dioxide, giving a certain roughness to the coating. When TEOS content is 0.16g, this roughness can not meet the requirement of super-hydrophobicity, and when TEOS content improves, the requirement of super-hydrophobicity reached by the coating surface roughness, thereby the water contact angle surges. The fluorosilicone polymer emulsion of the application embodies super-hydrophobicity when TEOS content is 0.20g and 0.24g, and its water contact angle is 152.3 °, which is greater than the water contact angle evaluation standard 150 ° of super-hydrophobic surface.
[0084] From the above implementation process, it can be seen that the present invention uses methyl methacrylate, butyl methacrylate, octadecyl methacrylate, 3-(trimethoxysilyl)propyl methacrylate and a short fluorocarbon chain fluorine-containing methacrylate monomer as monomers for emulsion polymerization to carry out polymerization reaction, and uses tetraethyl silicate for modification to obtain a fluorosilicone acrylate polymer emulsion, and selects methyl methacrylate and butyl methacrylate as the core structure, and the two work together to provide heat resistance and solvent resistance, so that the core-shell structure has a certain stability; the structure of octadecyl methacrylate is introduced into the molecule, the amount of fluorine-containing unsaturated monomers is reduced, the cost of the polymer system is reduced to a certain extent, and the hydrophobicity of the polymer is further improved; the silicon-containing acrylate monomer is introduced into the molecule, so that the polymer can react with tetraethyl silicate, so that a structure similar to silicon dioxide exists in the polymer, and the roughness of the film can be increased during film formation, and the hydrophobicity of the polymer is further improved; the process obtained by the present invention is simple, low-cost, and has good repeatability, and has low surface free energy and excellent hydrophobicity, which can achieve both economy and functionality.
[0085] In summary, the polymer emulsion prepared by the present invention reduces the cost of the polymer system to a certain extent, and improves the environmental protection of the polymer itself while maintaining excellent hydrophobic properties; the coating or modified coating obtained by the present invention has a simple synthesis process, good repeatability, low raw material cost, low surface free energy and excellent hydrophobic properties, and can achieve both economy and functionality.
[0086] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.
Claims
1. A fluorosilicone acrylate polymer emulsion, characterized in that: The emulsion has a core-shell structure, and its core phase is a polymer having the following general chemical structure formula: Wherein, R is hydrogen or methyl, R1 and R2 are each selected from any group of C1 to C18 alkyl, m = any integer in the range of 30 to 50, and n = any integer in the range of 80 to 100; The shell phase is a polymer having the following general chemical structure: Wherein, R is hydrogen or methyl, R3 and R4 are selected from any group of C1~C18 alkyl, R5 is selected from any group of C12~C18 alkyl, Rf is a group having a C(CF3)2CF2CF2CF3 structure, m=any integer in the range of 40~50, n=any integer in the range of 40~50, a=any integer in the range of 30~40, b=any integer in the range of 4~20, and c=any integer in the range of 10~20.
2. A method for preparing the fluorosilicone acrylate polymer emulsion according to claim 1, characterized in that: The specific steps include: (1) Acrylate monomer The reaction is heated in a solvent to produce product Ⅰ; (2) Add acrylic acid ester monomer and fluorinated acrylate monomers And silicon-containing acrylate monomers The product II is generated by heating the reaction in a solvent; (3) Mixing product I with an emulsifier and an initiator in a reactor, adding product II after initiation to continue the polymerization reaction, and finally adding tetraethyl silicate to modify the surface layer to obtain the fluorosilicone acrylate polymer emulsion.
3. The method according to claim 2, characterized in that Acrylate Monomers The weight ratio of the fluorine-containing acrylate monomer to the silicon-containing acrylate monomer is 1:2 to 1:10; the weight ratio of the fluorine-containing acrylate monomer to the silicon-containing acrylate monomer is 1:1.4 to 5:1.
4.
4. The method according to claim 2, characterized in that The weight ratio of tetraethyl silicate to silicon-containing acrylic ester monomer is 0.8:1.4 to 1.6:1.
4.
5. The method according to claim 2, characterized in that In step (1) and step (2), the reaction temperature is 40-60° C. and the reaction time is 30-60 min.
6. The method according to claim 2, characterized in that Acrylate Monomers and acrylic monomers The molar ratio is 2:
1.
7. The method according to claim 2, characterized in that In step (3), the polymerization reaction temperature is 70 to 100° C. and the time is 10 to 30 hours.
8. The method according to claim 2, characterized in that The added amount of the initiator is 0.1% to 3% of the total weight of the monomers; the added amount of the emulsifier is 3% to 4% of the total weight of the monomers.
9. The method according to claim 2, characterized in that The initiator is selected from one or more of organic peroxides, inorganic peroxides and azo compounds; the emulsifier is selected from one or more of anionic emulsifiers, cationic emulsifiers and nonionic emulsifiers.
10. A coating, characterized in that: The invention is prepared by coating the fluorosilicone acrylate polymer emulsion as claimed in claim 1 and then drying it.
Citation Information
Patent Citations
Fluorine-silicon modified self-crosslinking acrylic ester emulsion and preparation thereof
CN101348595A
Long side chain organosilicon modified fluorine-containing (methyl) acrylic acid ester polymer emulsion
CN103396509A
Core-shell type short-chain fluorine-containing acrylate emulsion and preparation method thereof
CN105440201A
Water-based fluorinated acrylate copolymer and hybrid membrane, and preparation methods and application thereof
CN110540614A
Cited By
Fluorine-containing methacrylate polymer modified epoxy resin coating and preparation method thereof
CN120441750A